PENGARUH EARNING PER SHARE DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN - Rakhmi Ridhawati; Mega Andani; Hanifah Hanifah (JURNAL KINDAI, 2025)
This study investigates the influence of Earnings Per Share (EPS) and firm size on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The research focuses on how earnings per share and firm size influence the stock prices of banking companies. The research method employed is quantitative. Analysis was conducted through hypothesis testing using multiple linear regression. The empirical findings reveal that EPS exerts a significant positive impact on stock prices. However, the results indicate that firm size does not substantially affect the stock performance of the surveyed banking institutions for the period 2022 to 2024. Keywords: Earnings Per Share (EPS), firm size, stock price